2012
DOI: 10.3390/ijerph9041427
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity among Puerto Rican Children: Discrepancies Between Child’s and Parent’s Perception of Weight Status

Abstract: Public concern about childhood obesity and associated health problems calls for the identification of modifiable factors that could halt this epidemic. Parental perceptions of their children’s weight status could be associated to how parents influence children’s eating patterns. We aimed to identify the perceptions Puerto Rican parents have of their children’s weight and children’s own perceptions of weight status as compared to real weight. A cross sectional survey was performed in a representative sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…Demographic characteristics of parents have been highlighted as predictors of accuracy in determining a child's weight status. Some studies have found that higher parental education level was associated with better accuracy in determining a child's weight status, whereas others have found race/ethnicity to be an important indicator of child weight misperceptions. In one study about the effectiveness of BMI report cards to improve accuracy of parents' perceptions, misperceptions were higher for African American than Caucasian parents at baseline; yet, African American parents also showed the greatest improvement in accuracy upon follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics of parents have been highlighted as predictors of accuracy in determining a child's weight status. Some studies have found that higher parental education level was associated with better accuracy in determining a child's weight status, whereas others have found race/ethnicity to be an important indicator of child weight misperceptions. In one study about the effectiveness of BMI report cards to improve accuracy of parents' perceptions, misperceptions were higher for African American than Caucasian parents at baseline; yet, African American parents also showed the greatest improvement in accuracy upon follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…But parents and pediatricians often underestimate children's body size (Akerman et al, 2007;Chaimovitz et al, 2008;Jones et al, 2011;Lampard et al, 2008;Parry et al, 2008;Perrin et al, 2005;Spurrier et al, 2006;Tschamler et al, 2010;Wald et al, 2007). Unrecognized obesity is especially high for obese parents, for overweight as compared to obese children (Taveras et al, 2011), for lower socioeconomic parents (Rivera-Soto and Rodriguez-Figueroa, 2012) and for Hispanics (Intagliata et al, 2008), African Americans (West et al, 2008) and Native Americans (Arcan et al, 2012) and could impair parental motivation to adopt weight control measures (Vuorela et al, 2010) and to participate in obesity reduction programs (Taveras et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it appears that the prevalence of inaccuracy is high in comparison to studies that have surveyed schoolchildren of different age groups and using other assessment tools, in which reported prevalence rates range from 22.6% to 58.0%. 4,22,[31][32][33][34] It is important to stress that the questionnaires used as evaluation instruments in these studies have not been validated for this use and so the discrepancies between prevalence results may be related to greater sensitivity of the instrument used in the present study. Notwithstanding these methodological differences, it is necessary to carry out studies to evaluate whether The present study revealed a greater chance of body underestimation among both boys and girls with obesity according to BMI, and a greater chance of body overestimation among girls with central obesity.…”
Section: Discussionmentioning
confidence: 99%